(untitled) (SAARC Journal of Agriculture, 2019)
A study was conducted to evaluate the effect of combined application of urea and poultry manure(viz., 100% N-urea, 75% N-urea + 25% N-PM, 50% N-urea + 50% N-PM, 25% N-urea + 75% N-PM and 100% N-PM) on yield and quality of two varieties of lettuce viz., Green Span and NAI RE KUI DA F1at the Horticulture Farm of Agriculture and Forestry University, Rampur, Chitwan, Nepal from October 30, 2015 to January 30, 2016. Results revealed that the integration of 50% or more N-PM had significantly higher values in growth, yield and quality parameters while the use of 100% N-urea had the lowest one. Similarly, the two varieties significantly differed in all characters and the variety Green Span performed better at all levels of integration of N-urea with N-poultry manure than NAI RE KUI DA F1. Based on interaction effect, Green Span performed better with 100% N-poultry manure while NAI RE KUI DA F1 did better with the combination of 50% N-urea and 50% N-PM. SAARC J. Agri., 17(1): 201-210 (2019)